2000
DOI: 10.1097/00005768-200005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 17??-methyltestosterone on myocardial function in vitro

Abstract: Testosterone analogs have been used as performance enhancers by athletes for more than 40 yr. We asked whether the anabolic steroid 17 alpha-methyl-4-androstene-17-ol-3-one (17 alpha-MT) would affect intrinsic contractile function of the heart. Male Sprague-Dawley rats, 125-150 g, were treated with 17 alpha-MT either parenterally or orally for up to 8 wk. Intrinsic contractile function of the hearts was assessed utilizing both the isolated working heart and isovolumic perfused heart preparations. Isolated work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
2
16
2
5
Order By: Relevance
“…This is not surprising given in vitro data that LOX treatment of isolated collagen gels resulted in a significant increase in GЈ (12,22). In vivo studies of rat heart and aorta also showed that increased stiffness was secondary to cross-linking by members of the LOX family rather than to increased collagen deposition (4,30,37).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This is not surprising given in vitro data that LOX treatment of isolated collagen gels resulted in a significant increase in GЈ (12,22). In vivo studies of rat heart and aorta also showed that increased stiffness was secondary to cross-linking by members of the LOX family rather than to increased collagen deposition (4,30,37).…”
Section: Discussionmentioning
confidence: 83%
“…This is a dosing strategy demonstrated in the literature to provide effective serum levels of the drug (30). BAPN was started 24 h before the first injection of CCl 4 and continued throughout the study, until the time of death (up to 14 days).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Im einen Fall hatte sich die Verkürzungsfraktion 9 Monate nach Absetzen des Anabolikums annähernd normalisiert [79]. Im Tierexperiment wurde eine Einschrän-kung der systolischen Funktion unter AAS nachgewiesen [61,88,92,103].…”
Section: Systolische Und Diastolische Linksventrikuläre Funktionunclassified
“…The use of MT on humans has been reported to have side effects, such as muscle damage (Hassan et al, 2009) and lower heart beating (Legros et al, 1999). Similarly, the testosterone hormone may influence the aggressiveness level of fish (Zairin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%